ENACTING MATHEMATICAL DISPOSITION: EXPLORING HOW STUDENTS WITH HIGH MATHEMATICAL LITERACY ENGAGE IN MATHEMATICAL LITERACY TASKS - Rustam Effendy Simamora; Ayu Ningsih; Alfian Mucti; Shinta Wulandari (MATEMATIKA DAN PEMBELAJARAN, 2026)
Mathematical disposition (MD) is widely recognized as a key factor influencing students’ performance, particularly in mathematical literacy (ML), which is emphasized in Indonesian education through the Asesmen Kompetensi Minimum (AKM), a national assessment focusing on literacy and numeracy. However, most studies rely on quantitative approaches, offering limited insight into how MD is enacted during problem-solving in classroom contexts. This study explores how MD is enacted by students with high ML when engaging in mathematical literacy tasks. Using a qualitative multiple-case study design, five senior high school students were purposively selected. Data were collected through written work, self-assessments, observations in individual and group settings, and two phases of interviews, and analyzed using thematic analysis. The findings reveal that MD emerges as a dynamic, context-sensitive system involving curiosity, confidence, persistence, flexibility, and reflection. Although all students produced correct solutions, their depth of engagement varied depending on how these dispositions were activated and regulated. Collaborative settings reshaped MD by redistributing confidence and enhancing participation, but also introduced challenges, such as reduced verification due to overreliance on group agreement. These findings suggest that ML provides the cognitive foundation for problem solving, while MD mediates its enactment.     Keywords: Mathematical Disposition; Mathematical Literacy; Problem-Solving; Qualitative Study; Task-Based Learning.